Optimization of simulated moving bed processes for multicomponent chiral separations - Ribeiro, António E. (2012)
This work will present and discuss the experimental and simulation results obtained for the analytical and preparative separation of the four stereoisomers of nadolol, an important example of a non-selective beta-adrenergic receptor antagonist (beta-blocker) pharmaceutical drug, widely used in the treatment of cardiovascular system diseases, such as hypertension, ischemic heart disease (angina pectoris), congestive heart failure and certain arrhythmias. The main focus will be placed in the selection of the proper CSP/solvent combination for SMB operation. Experimental results will be presented using Chiralpak AD and Chiralpak IA CSP (Daicel, Europe) and different mixtures of alkanes, alcohols and acetonitrile as solvent.